Міжнародна допомога відновленню Донецької області - Беззубко, Ю.І. (Вісник економічної науки України, 2020)
Міжнародна технічна допомога (МТД) сприяє вирішенню актуальних проблем країн. Міжнародна технічна допомога спрямована на відновлення Донецької області через наслідки військового конфлікту. Однак в сучасних умовах існує недостатнє опрацювання як теоретичних, так і практичних питань надання міжнародної допомоги в Україні. Метою статті є характеристика надання міжнародної технічної допомоги у процесах відновлення Донецької області. Проаналізована інформація про МТД (2016-2019 рр.). Визначені основні напрями МТД: отримання гуманітарної допомоги; підтримка розвитку підприємництва, розвиток освіти, відновлення інфраструктури закладів медицини і освіти. Під час дослідження було визначено наявність проблем із наданням і використанням МТД: недосконалість стратегічного планування надходжень МТД, координації діяльності між донорами та реципієнтами МТД; неузгодженість МТД із задачами, стратегіями і пріоритетами соціально-економічного розвитку України, завданнями сталого розвитку країни; відсутність нормативно-правового механізму отримання і використання МТД, ефективного моніторингу та оцінки використання МТД, прозорості у використанні МТД, узгодженості у роботі за проєктами МТД; неефективне використання коштів МТД. Визначено зовнішні та внутрішні чинники підвищення ефективності використання МТД. Запропоновано рекомендації – міжнародну технічну допомогу необхідно здійснювати на засадах: 1. Узгодження: із національними, регіональними та місцевими стратегіями; пріоритетами та завданнями відновлення Донецької області від наслідків військового конфлікту; діяльності донорів та реципієнтів МТД у процесах підготовки проєктів, контроля та моніторингу здійснення МТД. 2. Вдосконалення: методів управління МТД (процеси планування, бюджетування, контролю і моніторингу, розрахунок ефективності від використання МТД); нормативно-правової основи здійснення МТД (прийняття Закону України «Про міжнародну технічну допомогу»). 3. Врахування в державному бюджеті України ресурсів міжнародної технічної допомоги. 4. Впровадження механізму співфінансування МТД і програм відновлення. Международная техническая помощь (МТП) способствует решению актуальных проблем стран. Международная техническая помощь направлена на восстановление Донецкой области от последствий военного конфликта. Однако в современных условиях существует недостаточная проработка как теоретических, так и практических вопросов оказания международной помощи в Украине. Целью статьи является характеристика предоставления международной технической помощи в процессах восстановления Донецкой области. Проанализирована информация о МТД (2016-2019 гг.). Определены основные направления МТП: получение гуманитарной помощи; поддержка развития предпринимательства, развитие образования, восстановление инфраструктуры учреждений медицины и образования. В ходе исследования было определено наличие проблем с предоставлением и использованием МТП: несовершенство стратегического планирования поступлений МТП, координации деятельности между донорами и реципиентами МТП; несогласованность МТП с задачами, стратегиями и приоритетами социально-экономического развития Украины, задачами устойчивого развития страны; отсутствие нормативно-правового механизма получения и использования МТП, эффективного мониторинга и оценки использования МТП, прозрачности в использовании МТП, согласованности в работе по проектам МТП; неэффективное использование средств МТП. Определены внешние и внутренние факторы повышения эффективности использования МТП. Предложены рекомендации – осуществление международной технической помощи на основе: 1. Согласование: с национальными, региональными и местными стратегиями; приоритетами и задачами восстановления Донецкой области от последствий военного конфликта, деятельности доноров и реципиентов МТП в процессах подготовки проектов, контроля и мониторинга осуществления МТП. 2. Совершенствование: методов управления МТП (процессы планирования, бюджетирования, контроля и мониторинга, расчет эффективности использования МТП); нормативно-правовой базы осуществления МТП (принятие Закона Украины «О международной технической помощи»). 3. Учет в государственном бюджете Украины ресурсов международной технической помощи. 4. Внедрение механизма софинансирования МТП и программ восстановления. At present, ecological tourism as a priority area of the regional economy needs transformational transformations that will help increase the tourist competitiveness of the regions of Ukraine and sustainable development of territories. The purpose of this study is a comparative analysis of strategic documents in the development of ecotourism and infrastructure, taking into account regional characteristics. To achieve this goal, methods of analysis and synthesis, comparison, generalization, structural and logical analysis were used. The article analyses the strategies of regional development for 2021-2027. Based on the analysis, it is established that in a significant number of strategic documents the priority areas include accelerating the achievement of competitiveness and innovation of the region's economy on the basis of smart specialization. Regional strategies do not address the creation of appropriate conditions for the formation of the institutional environment for the development of ecotourism. Only in the Development Strategies of Lviv and Odesa oblasts, among the strategic goals, tourist attractiveness is recognized due to the formation of the appropriate infrastructure. At the same time, the term "rural green tourism" is most often used in tourism and recreation development programs implemented in most regions of Ukraine. It is proved that there are differences and inaccuracies in the applied terminology on the problems of ecotourism. The programs usually talk about the formation of tourist infrastructure, but do not say anything about the creation of ecotourism infrastructure. The mechanisms of organizational, economic, informational, financial support for the development of ecotourism activities are not prescribed. Therefore, it is expedient to make changes and additions to the Strategies of regional development until 2027 and programs for the development of tourism and recreation, the content of which is to include a set of measures to intensify the development of ecotourism and the formation of ecotourism infrastructure. This will create a positive tourist image of the regions of Ukraine; increase their competitiveness and investment attractiveness; to ensure the growth of employment and the share of tax revenues from business activities in the ecotourism sector; increase the number of domestic tourists, including "weekend" tourists, sales of regional tourist products, the number of tourist routes, the number of newly created ecotourism and recreational facilities, the number of employees in the tourism industry.